Gregarious suspension feeding in a modular Ediacaran organism - Gibson, Brandt M. (Sci Adv, 2019)
Reconstructing Precambrian eukaryotic paleoecology is pivotal to understanding the origins of the modern, animal-dominated biosphere. Here, we combine new fossil data from southern Namibia with computational fluid dynamics (CFD) to test between competing feeding models for the Ediacaran taxon Ernietta. In addition, we perform simulations for multiple individuals, allowing us to analyze hydrodynamics of living communities. We show that Ernietta lived gregariously, forming shallow marine aggregations in the latest Ediacaran, 548 to 541 million years (Ma) ago. We demonstrate enhanced vertical mixing of the water column above aggregations and preferential redirection of current into body cavities of downstream individuals. These results support the reconstruction of Ernietta as a macroscopic suspension feeder and also provide a convincing paleoecological advantage to feeding in aggregations analogous to those recognized in many extant marine metazoans. These results provide some of the oldest evidence of commensal facilitation by macroscopic eukaryotes yet recognized in the fossil record.